Specifics of Use of Internet Space in Election Campaigns ("Journal "U". Economy. Management. Finance.", 2017)
The article describes the main stages of development of the political Internet in Russia and provides their short characteristics. During the research work the authors have revealed a number of instruments of political campaign promotion on the Internet and on their basis considered pre-election propaganda activity of regional departments of parties «Edinaja Rossija», «Spravedlivaja Rossija», «KPRF», «LDPR» allocated in Rostov-on-Don and made conclusions about their efficiency.
Keywords: political Internet; political management; political Internet technologies; election campaign; elections